The home place : memoirs of a colored man's love affair with nature - Lanham, J. Drew (Joseph Drew) (2017)
"The Home Place is a remarkable meditation on nature and belonging. This is at once a deeply moving memoir and a riveting exploration of the contradictions of black identity in the rural South -- and in America today."--Inside cover
Me : an introduction -- FLOCK -- The home place -- Mamatha takes flight -- A good name -- A field guide to the four -- First-Sunday God -- FLEDGLING -- Little brown Icarus -- Whose eye is on the sparrow -- Cows -- Life's spring -- FLIGHT -- The bluebird of enlightenment -- Hoops -- Birding while black -- Jawbone -- New religion -- Thinking -- Digging -- Family reunion -- Patchwork legacy
Keywords: Lanham, J. Drew; Zoologists -- South Carolina -- Biography; African American zoologists -- South Carolina -- Biography; Conservationists -- South Carolina -- Biography; Autobiographies; Autobiographies; Biographies